Preparation method of bimetal organic framework material with hollow morphology

By chemically etching the bimetallic organic frame material with Tannic tannic, the problem that traditional methods are difficult to accurately control the size and morphology of hollow structures is solved, and the preparation of hollow morphology bimetallic organic frame material is realized. It has high specific surface area, low density and versatility, and is suitable for a variety of applications.

CN119912700APending Publication Date: 2025-05-02HENAN UNIV OF URBAN CONSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510075187.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional MOFs synthesis methods are difficult to accurately control the size and morphology of hollow structures, which limits its application in the fields of catalysis, gas adsorption and separation, drug delivery, etc.

Method used

By using Tannic (TA) as a chemical etchant, the core part of the bimetallic organic frame BZIF is selectively dissolved, and the hollow bimetallic organic frame material BZIF-TA is synthesized to achieve fine regulation of the internal structure and precise control of the hollow morphology.

Benefits of technology

The preparation of hollow morphological bimetallic organic frame materials has been realized, with high specific surface area, low density and versatility, suitable for adsorption, catalysis, drug delivery and other applications, and can be used to design better electrocatalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912700A_ABST
    Figure CN119912700A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of metal organic framework materials, and discloses a preparation method of a bimetal organic framework material with a hollow morphology, and the preparation method comprises the following steps: S1, preparing raw materials: tannic acid Tannic acid, a methanol solution of TA, zinc nitrate Zn < 2 + >, cobalt nitrate Co < 2 + > and 2-methylimidazole C4H6N2. A BZIF-TA hollow structure is obtained through the etching effect of tannic acid Tannic acid and TA on BZIF; according to the preparation method, fine regulation and control of the internal structure can be achieved, the structure and morphology of the hollow morphology can be accurately controlled, highly customized material design is achieved, preparation of the hollow morphology bimetal organic framework material is achieved, and the preparation method has the advantages of being high in practicability and accurate and convenient to obtain the hollow structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal organic framework material preparation, in particular to a method for preparing a hollow bimetallic organic framework material. Background Art

[0002] Metal-Organic Frameworks, or MOFs for short, are a class of porous crystalline materials formed by self-assembly of metal ions or metal clusters and organic ligands through coordination bonds. Due to their highly ordered pore structure, huge specific surface area and adjustable pore size, MOFs have shown broad application prospects in gas storage, separation, catalysis, sensing and drug delivery.

[0003] Although monometallic MOFs have shown excellent performance, the limitations of single metal sites have gradually become apparent in some applications. Bimetallic MOFs, by introducing a second metal, not only increase the number and diversity of active sites, but also produce a synergistic effect, thereby improving the catalytic activity, selectivity and other properties of the material. Bimetallic MOFs have shown superior performance to monometallic MOFs in catalysis, gas adsorption and separation.

[0004] Compared with solid structures, hollow MOFs have higher specific surface area, larger internal space and better mass transfer performance. These characteristics give hollow MOFs significant advantages in catalysis, gas adsorption and separation, drug delivery and other fields. However, traditional MOFs synthesis methods make it difficult to accurately control the size and morphology of the hollow structure when obtaining the hollow structure. Therefore, it is necessary to design a preparation method for hollow morphology bimetallic organic framework materials that is highly practical and can obtain hollow structures accurately and conveniently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a hollow bimetallic organic framework material to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a hollow bimetallic organic framework material, comprising the following steps: S1, raw material preparation: Tannic acid, methanol solution of TA, zinc nitrate Zn 2+ 、Cobalt nitrate Co 2+ , 2-methylimidazole C4H6N2; S2, solution preparation: Weigh 0.4 g zinc nitrate hexahydrate and 0.039 g cobalt nitrate nonahydrate respectively, dissolve them in 40 mL methanol, stir at a constant speed, and record it as solution A; weigh 1.85 g 2-methylimidazole and dissolve it in 40 mL methanol, ultrasonicate for 1 min, and record it as solution B; S3, solution mixing: while solution A is being stirred at a constant speed, solution B is poured into the stirred solution A, and after mixing, the mixture is stirred at room temperature for 24 hours to generate a bimetallic organic framework BZIF composed of ZIF-8 / ZIF-67; S4, product formation: washing the product multiple times with a detergent to remove unreacted raw materials and by-products, and centrifugation washing to obtain BZIF particles of uniform size; S5, wet etching: using chemical etchant TA to selectively dissolve the core part of the bimetallic organic framework BZIF10, and utilizing the etching effect of TA on the metal organic framework structure, a hollow bimetallic organic framework composite material named BZIF-TA was synthesized; S6, dosage calculation: a certain amount of BZIF powder is simply mixed with a methanol solution of TA of a certain concentration and stirred for a certain period of time. During this process, the concentration and dosage of TA are adjusted, and the resulting product is analyzed under a transmission electron microscope to optimize the morphology of the final product.

[0007] According to the above technical scheme, in steps S2-S4, the Zn in zinc nitrate and cobalt nitrate is 2+ 、Co 2+ BZIF10, BZIF20 and BZIF40 were synthesized by using different molar ratios of Zn 2+ :Co 2+ =10:1.

[0008] According to the above technical solution, in step S6, for every 20 mg of BZIF particles, the volume of TA / methanol used was set to 0.833 mL, 1.667 mL, 3.333 mL and 5 mL, respectively, and the concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L.

[0009] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The hollow structure of BZIF-TA was obtained by etching BZIF with tannic acid (TA). The steps are simple and can achieve fine regulation of the internal structure. The structure and morphology of the hollow morphology can be precisely controlled, and highly customized material design can be achieved. The preparation of hollow morphology bimetallic organic framework materials is realized. This hollow morphology bimetallic organic framework material has many advantages, such as high specific surface area: hollow morphology materials usually have a very high specific surface area, which is very important for applications such as adsorption, catalysis, and drug delivery; low density: due to the cavity inside, the density of hollow morphology materials is usually low, which has advantages in reducing weight while maintaining strength; multifunctionality: by changing the size, shape, and distribution of the cavity, the material can be given different functions, such as enhanced mechanical properties, improved conductivity, enhanced catalytic activity, etc. (2) Hollow state BZIFn-TA (n is Zn 2+ / Co 2+ =10 / 20 / 40) chain-like precursors, such precursors have mesopores provided by the BZIF hollow core itself, and macropores formed by BZIF connection. At the same time, the two-dimensional chains are superimposed in space, which can be used as precursors for loading metal ions, and can be subsequently applied to the design and synthesis of carbon-based / metal composite catalysts; (3) In addition, this substrate can be combined with other types of transition metal ions to design and synthesize bifunctional or even trifunctional electrocatalysts with better performance and more functions. For example, by further introducing Fe 3+ , due to TA and Co 2+ and Fe 3+ The strong chelation between TA molecules and Fe 3+ 、Co 2+ They can all be combined, and after freeze-drying, high-temperature sintering and acid treatment, carbon-based composite catalysts loaded with Fe and Co can be prepared. Thanks to the spatial confinement effect of TA molecules, it can assist in the synthesis of carbon materials loaded with ultra-small transition metals such as single atoms, nanoclusters, and ultra-small particles. These ultra-small metal species provide more active sites, thereby enhancing the overall catalytic performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 Schematic diagram of transmission electron microscopy of BZIF10-TA under different conditions of the present invention; Figure 2 Schematic diagram of the product morphology obtained under different mass ratios of BZIF10:TA of the present invention; Figure 3 It is a transmission electron microscope schematic diagram of BZIF10-TA in the critical value state of the present invention; Figure 4 It is a transmission electron microscope schematic diagram of BZIF10-TA, BZIF20-TA and BZIF40-TA of the present invention; Figure 5 Schematic diagram of LSV curves of ORR of carbon materials obtained after pyrolysis of different BZIF-TA precursors of the present invention; Figure 6 Schematic representation of the half-wave potential and onset potential of the carbon material obtained after pyrolysis of different BZIF-TA precursors of the present invention; Figure 7Schematic diagram of LSV curves of HER for carbon materials obtained by directly sintering different BZIF-TA precursors of the present invention; Figure 8 This is a schematic diagram of the LSV of the FeCo / C catalyst for ORR obtained by sintering BZIF20-TA as a precursor and adjusting the Fe:Co molar ratio to 1:3 / 1:4 / 1:8; Fig. 9 Schematic representation of the half-wave potential and onset potential of the FeCo / C catalyst obtained with different Fe:Co molar ratios of the present invention; Fig.10 It is a schematic diagram of the LSV of the FeCo / C catalyst for HER obtained by sintering BZIF20-TA as a precursor and adjusting the Fe:Co molar ratio to 1:2 / 1:3 / 1:4 / 1:6 / 1:8; Fig.11 Schematic representation of the overpotential of the electrocatalysts obtained with different Fe:Co molar ratios of the present invention; DETAILED DESCRIPTION

[0011] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] See also Figure 1-11 The present invention provides a technical solution: a method for preparing a hollow bimetallic organic framework material, comprising the following steps: S1, raw material preparation: Tannic acid, methanol solution of TA, zinc nitrate Zn 2+ 、Cobalt nitrate Co 2+ , 2-methylimidazole C4H6N2; S2, solution preparation: Weigh 0.4 g zinc nitrate hexahydrate and 0.039 g cobalt nitrate nonahydrate respectively, dissolve them in 40 mL methanol, stir at a constant speed, and record it as solution A; weigh 1.85 g 2-methylimidazole and dissolve it in 40 mL methanol, ultrasonicate for 1 min, and record it as solution B; S3, solution mixing: while solution A is being stirred at a constant speed, solution B is poured into the stirred solution A, and after mixing, the mixture is stirred at room temperature for 24 hours to generate a bimetallic organic framework BZIF composed of ZIF-8 / ZIF-67; S4, product formation: washing the product multiple times with a detergent to remove unreacted raw materials and by-products, and centrifugation washing to obtain BZIF particles of uniform size; S5, wet etching: using chemical etchant TA to selectively dissolve the core part of the bimetallic organic framework BZIF, and utilizing the etching effect of TA on the metal organic framework structure, a hollow bimetallic organic framework composite material named BZIF-TA was synthesized; S6, dosage calculation: a certain amount of BZIF powder is simply mixed with a methanol solution of TA of a certain concentration and stirred for a certain period of time. During this process, the concentration and dosage of TA are adjusted, and the resulting product is analyzed under a transmission electron microscope to optimize the morphology of the final product.

[0013] Specifically, in steps S2-S4, the Zn in zinc nitrate and cobalt nitrate 2+ 、Co 2+ BZIF10, BZIF20 and BZIF40 were synthesized by using different molar ratios of Zn 2+ :Co 2+ =10:1; Specifically, in step S6, for every 20 mg of BZIF particles, the volume of TA / methanol used was set to 0.833 mL, 1.667 mL, 3.333 mL and 5 mL, respectively, and the concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L.

[0014] Working principle: The hollow structure of BZIF-TA is obtained by etching BZIF with tannic acid (TA), which can achieve fine regulation of the internal structure, accurately control the structure and morphology of the hollow morphology, realize highly customized material design, and realize the preparation of hollow morphology bimetallic organic framework materials. Hollow morphology bimetallic organic framework materials have many advantages, such as high specific surface area: hollow morphology materials usually have a very high specific surface area, which is very important for applications such as adsorption, catalysis, and drug delivery; low density: due to the cavity inside, the density of hollow morphology materials is usually low, which has advantages in reducing weight while maintaining strength; multifunctionality: by changing the size, shape and distribution of the cavity, different functions can be given to the material, such as enhanced mechanical properties, improved conductivity, enhanced catalytic activity, etc. Figure 1 Figure 1 is a schematic diagram of transmission electron microscopy of BZIF10-TA under different conditions of the present invention, the conditions are set to a(5gL -1 , 0.833mL), b(6gL -1 , 0.833mL), c(8gL -1 , 0.833mL), d(5gL -1 , 1.667mL), e(6gL -1 , 1.667 mL), stirred for 4 h, f (8 g L -1 , 1.667mL), g(5gL-1 , 3.333mL), h(6gL -1 , 3.333mL), i(8gL -1 , 3.333mL), j5gL -1 , 5mL, k(6gL -1 , 5mL), l(8gL -1 , 5 mL), stirred for 24 h; Figure 3 The condition was set to 5 gL -1 , 2.667mL; Figure 4 The conditions were set as aBZIF10-TA, bBZIF20-TA, cBZIF40-TA, where TA / methanol = 8 gL -1 ; According to the attached drawings in the specification Figure 1 and Figure 2 ,like Figure 1 As shown in Fig. ac, for every 20 mg of BZIF10 particles, the volume of TA / methanol used was 0.833 mL. The concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L. As the volume of TA / methanol used increased, BZIF10 was bonded by a solid shell and then changed into a core-shell shape; Figure 1 As shown in df, for every 20 mg of BZIF10 particles, the volume of TA / methanol used was 1.667 mL. The concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L. As the volume of TA / methanol used increased, BZIF10 changed from a core-shell shape to a hollow sphere; Figure 1 As shown in gi, for every 20 mg of BZIF10 particles, the volume of TA / methanol used was 3.333 mL. The concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L. As the volume of TA / methanol used increased, the shell layer of BZIF10 with core-shell morphology gradually thickened. Similarly, Figure 1 As shown in Figure jl, for every 20 mg of BZIF10 particles, the volume of TA / methanol used was 5 mL. When the concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L, the shell of BZIF10 with core-shell morphology became thicker. It can be concluded that whether BZIF10 can be etched into a hollow structure has nothing to do with the concentration of TA / methanol, but is related to the total amount of TA in the solution. For verification, we selected the critical value BZIF-10:TA=1:0.667, the concentration of TA / methanol was 8 g / L, and the total amount of TA was converted into 5 g / L TA / methanol solution, and the corresponding volume increased from 1.667 mL to 2.667 mL. For every 20 mg of BZIF10, the total mass of TA in the solution was 13.336 mg. BZIF10 was treated under the same conditions. The results showed that BZIF-10 was well corroded. Figure 3 As shown, it is concluded that whether BZIF10 can be etched into a hollow structure has nothing to do with the concentration of TA / methanol, but is related to the total amount of TA in the solution; We extended the condition of BZIF-10:TA=1:0.667 and TA / methanol concentration of 8 g / L to BZIF20 and BZIF40. Figure 4 As shown in the figure, under the same conditions, stirring for 4 h also gave BZIF20-TA and BZIF40-TA with good corrosion. In this way, we obtained BZIFn-TA (n is Zn 2+ / Co 2+ =10 / 20 / 40) chain-like precursors, such precursors have mesopores provided by the BZIF hollow core itself, and macropores formed by BZIF connection. At the same time, the two-dimensional chains are superimposed in space, which can be used as precursors for loading metal ions, and can be subsequently applied to the design and synthesis of carbon-based / metal composite catalysts; We have obtained the hollow structure of BZIF-TA by etching BZIF with TA. At the same time, due to the strong interaction of TA with various transition metal ions Fe / Co / Ni, some Co as the metal center of BZIF 2+ After being released and tightly combined with TA, the carbon material obtained after pyrolysis can itself have certain electrocatalytic activity in oxygen reduction reaction ORR, hydrogen evolution reaction HER and oxygen evolution reaction OER; In addition, this substrate can be combined with other types of transition metal ions to design and synthesize bifunctional or even trifunctional electrocatalysts with better performance and more functions. For example, by further introducing Fe 3+ , due to TA and Co 2+ and Fe 3+ The strong chelation between TA molecules and Fe 3+ 、Co 2+They can all be combined, and after freeze-drying, high-temperature sintering and acid treatment, carbon-based composite catalysts loaded with Fe and Co can be prepared. Thanks to the spatial confinement effect of TA molecules, it can assist in the synthesis of carbon materials loaded with ultra-small transition metals such as single atoms, nanoclusters, and ultra-small particles. These ultra-small metal species provide more active sites, thereby enhancing the overall catalytic performance of the material.

[0015] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0016] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hollow bimetallic organic framework material, characterized in that: The following steps are involved: S1, raw material preparation: Tannic acid, methanol solution of TA, zinc nitrate Zn 2+ 、Cobalt nitrate Co 2+ , 2-methylimidazole C4H6N2; S2, solution preparation: Weigh 0.4 g zinc nitrate hexahydrate and 0.039 g cobalt nitrate nonahydrate respectively, dissolve them in 40 mL methanol, stir at a constant speed, and record it as solution A; weigh 1.85 g 2-methylimidazole and dissolve it in 40 mL methanol, ultrasonicate for 1 min, and record it as solution B; S3, solution mixing: while solution A is being stirred at a constant speed, solution B is poured into the stirred solution A, and after mixing, the mixture is stirred at room temperature for 24 hours to generate a bimetallic organic framework BZIF composed of ZIF-8 / ZIF-67; S4, product formation: washing the product multiple times with a detergent to remove unreacted raw materials and by-products, and centrifugation to obtain BZIF particles of uniform size; S5, wet etching: using chemical etchant TA to selectively dissolve the core part of the bimetallic organic framework BZIF, and utilizing the etching effect of TA on the metal organic framework structure, a hollow bimetallic organic framework composite material named BZIF-TA was stably synthesized; S6, dosage calculation: a certain amount of BZIF powder is simply mixed with a methanol solution of TA of a certain concentration and stirred for a certain period of time. During this process, the concentration and dosage of TA are adjusted, and the resulting product is analyzed under a transmission electron microscope to optimize the morphology of the final product.

2. The method for preparing a hollow bimetallic organic framework material according to claim 1, characterized in that: In steps S2-S4, the Zn in zinc nitrate and cobalt nitrate is 2+ 、Co 2+ BZIF10, BZIF20 and BZIF40 were synthesized by using different molar ratios of Zn 2+ :Co 2+ =10:

1.

3. The method for preparing a hollow bimetallic organic framework material according to claim 1, characterized in that: In step S6, for every 20 mg of BZIF particles, the volume of TA / methanol used was set to 0.833 mL, 1.667 mL, 3.333 mL and 5 mL, respectively, and the concentration of TA / methanol was changed from 5 g / L, 6 g / L to 8 g / L.